Encyclopedia of governance - Bevir, Mark (Gale virtual reference library, 2007)
Comprehensive resource for the diverse and complex topics surrounding governance for the period between the collapse of the post-war consensus and the rise of neoliberal regimes in the 1970's. Concentrates primarily on topics related to the changing nature and role of the state in recent times and the ways in which these roles have been conceptualized in the areas of political science, public administration, political economy, and sociology.